Skilled migration: Bridging the conceptual gap between friendship, social capital, and employability - Danielle Potts; Malte Martensen (IUBH Internationale Hochschule, 2020)
Germany's population is currently undergoing a major shift as well as a general decline. These changes are expected to impact not only the workforce but also the social systems dependent on having a steady supply of individuals contributing to them. While no single solution alone is likely to be enough to resolve the upcoming challenges, the post-graduation employment of international students may help. However, even though there are jobs available, many international students in Germany struggle to find work after completing their studies. How, and with who, international students form their networks in the host country may play a crucial role in successful employment. While research has been conducted on international student friendship formation, social capital, and employability, little to no research has been conducted on how these elements interact when employment in the host country is the goal of an international student post-graduation. A better understanding of the role friendship plays in developing host country social capital could be key in guaranteeing international students to find employment in their host country post-graduation. Additionally, for Germany in particular, this will mean more filled positions and potentially reduced strain on workforce dependent social systems in the future.
Keywords: M54; 650; International Students; Friendship Formation; Social Capital; Employability; Germany